2007
DOI: 10.1016/j.ejvs.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Graft Infection by Staphylococcus aureus: Efficacy of Cefazolin, Teicoplanin and Vancomycin Prophylaxis Protocols in a Rat Model

Abstract: As a prophylactic agent, teicoplanin seems to be more effective than vancomycin and cefazolin against vascular graft infections caused by MSSA and MRSA in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
0
18
0
5
Order By: Relevance
“…Reports from the basic science literature describe polymers capable of releasing varied antibiotics such as cefazolin and vancomycin [5,[26][27][28]. These studies generally have a maximum follow-up period of 14 d and use primarily diffusion-based drug delivery polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from the basic science literature describe polymers capable of releasing varied antibiotics such as cefazolin and vancomycin [5,[26][27][28]. These studies generally have a maximum follow-up period of 14 d and use primarily diffusion-based drug delivery polymers.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Classic management of this challenging problem includes complete removal of a prosthetic implant with extra-anatomic reconstruction. 5 Other management strategies have included selected in situ replacement or graft preservation.…”
mentioning
confidence: 99%
“…40,41 Teicoplanin has a similar antibacterial spectrum similar to that of vancomycin, but a longer half-life and a lower risk of serious side effects. 42−46 Atahan et al 47 reported that teicoplanin shows superior effects in vascular graft infection with MSSA and MRSA compared to vancomycin.…”
Section: Discussionmentioning
confidence: 99%